(untitled) (CIPEEX, 2025)
This article deals with land regularization and demarcation of indigenous lands, and aims to demonstrate the benefits and challenges that irregular land owners face to legalize land ownership, especially the demarcation of indigenous lands, a discussed topic that generates insecurity and land conflicts in the country. Land regularization is a set of legal measures that seeks to bring to the legal world what is consolidated in the factual world, and the demarcation of indigenous lands is still a challenge. The owner holds possession of the property but ends up in a vulnerable and very risky situation, because he is occupying the land irregularly, creating legal uncertainty. Therefore, there is no doubt that public policies act in communion with public and private interests in encouraging regularization through deeds at the property registry office. As a method, the research was developed with the analysis of various topics regarding land regularization and demarcation of indigenous lands, it was developed through books, congresses, and news websites. As a result, it is clear that land regularization is based on the dignity of the human person, is essential for legal stability and social pacification and indigenous lands are still a challenge. In a strict sense, land regularization consists of a set of measures aimed at providing titles to rural workers, who produce food in public areas. The title granted will provide the occupant with access to essential public policies, such as agricultural financing and programs to encourage production in the countryside. Its scope is restricted to public and vacant lands (HAVRENNE, 2018). Furthermore, it is worth mentioning that indigenous peoples are those who inhabited the country at the time of conquest or colonization and when it comes to regularizing the lands of these peoples, a widely discussed point is the existence or not of the time frame. Land is fundamental in the recognition of indigenous identity. According to a study published on the gov.com website, indigenous lands are the most preserved areas in Brazil, as they are prone to less carbon loss through degradation. In this context, the demarcation of indigenous lands is the guarantee of the country’s future, on the other hand, Brazil still requires a lot of organization. It is concluded, therefore, that land regularization and the demarcation of indigenous lands is of utmost relevance both for the rural owner who is assured of legal stability, reduced conflicts, access to credit for investment and social development in the countryside, as well as to guarantee lands and preserve the identity of indigenous peoples. Therefore, it is essential that the State, in communion with the private sector, promotes incentive actions to regulate properties through legislation and public policies. Therefore, by actually knowing who owns the property through the legitimization of ownership, the right to property will no longer be a utopia.